Women's patronage and gendered cultural networks in early modern Europe Vittoria della Rovere, Grand Duchess of Tuscany - Modesti, Adelina (Visual culture in early modernity, 2020)
"This book examines the socio-cultural networks between the courts of early modern Italy and Europe, focusing on the Florentine Medici court, and the cultural patronage and international gendered networks developed by the Grand Duchess of Tuscany, Vittoria della Rovere. Adelina Modesti uses Grand Duchess Vittoria as an exemplar of pan-European matronage and proposes a new matrilineal model of patronage in the early modern period, one in which women become not only the mediators but also the architects of public taste and the transmitters of cultural capital. The book will be the first comprehensive monographic study of this important cultural figure. This study will be of interest to scholars working in art history, gender studies, Renaissance studies, and seventeenth century Italy"--